Timing of in utero malaria exposure influences fetal CD4 T cell regulatory versus effector differentiation. (December 2016) - Prahl, Mary; Jagannathan, Prasanna; McIntyre, Tara; Auma, Ann; Farrington, Lila; Wamala, Samuel; Nalubega, Mayimuna; Musinguzi, Kenneth; Naluwu, Kate; Sikyoma, Esther; Budker, Rachel; Vance, Hilary; et al.
Abstract Background In malaria-endemic areas, the first exposure to malaria antigens often occurs in utero when the fetal immune system is poised towards the development of tolerance. Children exposed to placental malaria have an increased risk of clinical malaria in the first few years of life compared to unexposed children. Recent work has suggested the potential of pregnancy-associated malaria to induce immune tolerance in children living in malaria-endemic areas. A study was completed to evaluate the effect of malaria exposure during pregnancy on fetal immune tolerance and effector responses. Methods Using cord blood samples from a cohort of mother-infant pairs followed from early in pregnancy until delivery, flow cytometry analysis was completed to assess the relationship between pregnancy-associated malaria and fetal cord blood CD4 and dendritic cell phenotypes. Results Cord blood FoxP3+ Treg counts were higher in infants born to mothers withPlasmodium parasitaemia early in pregnancy (12–20 weeks of gestation; p = 0.048), but there was no association between Treg counts and the presence of parasites in the placenta at the time of delivery (by loop-mediated isothermal amplification (LAMP); p = 0.810). In contrast, higher frequencies of activated CD4 T cells (CD25+ FoxP3− CD127+ ) were observed in the cord blood of neonates with active placentalPlasmodium infection at the time of delivery (p = 0.035). This population exhibited evidence of effector memory differentiation, suggesting priming of effector T cells in utero. Lastly, myeloid dendritic cells were higher in the cord blood of infants with histopathologic evidence of placental malaria (p < 0.0001). Conclusion Together, these data indicate that in utero exposure to malaria drives expansion of both regulatory and effector T cells in the fetus, and that the timing of this exposure has a pivotal role in determining the polarization of the fetal immune response.